Analysis of trends and projections of food production and consumption in Brazil and Nigeria. - Paulino, Leonardo A.; Sarma, J. S. (International Food Policy Research Institute, 1988)
IFPRI's food gap studies ... aimed at defining the general magnitude, composition, and dynamics of the Third World food problem, have primarily used agricultural data furnished by ...( FAO)--P. vii.